Pengaruh Model Pembelajaran Berbasis Masalah Dengan Pembekalan Pengetahuan Awal Terhadap Keterampilan Proses Sains Peserta Didik SMA - Nurul Hikmawati; Sutrio Sutrio; Hikmawati Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to determine the effect of problem based learning model with debriefing prior knowledge of the science process skills of learners. This research is a quasi experimental research using non-equivalent control group design. The population in this study is all students of class XI IPA SMAN 1 Montong Gading. The sampling of the research using saturated sampling technique, so that the selected class XI IPA 1 as the experimental class will be given treatment in the form of problem-based learning model with initial knowledge knowledge and class XI IPA 2 as the control class to be given treatment in the form of problem-based learning model. Data collection of science process skills using observation techniques on the observation sheet. Hypothesis test using t-pooled variance test obtained tcount value is greater than ttable. The result of the research shows that the use of problem-based learning model with prior knowledge sharing influences the science process skill of SMA students.